ARS ADEO LATET ARTE SUA : AUTOUR DE L’ÉLÉGIE CRYPTOLOGIQUE 3.14 DES TRISTES D’OVIDE ET D’HYGIN, PRÉFET DE LA BIBLIOTHÈQUE PALATINE - Gauthier Liberman (Exemplaria Classica, 2018)
We try to corroborate Rudolf Merkel’s idea that Ovid’s friend, the philologist and prefect of the Palatine Library Hyginus is actually the addressee of the last poem of book 3 of the Tristia collection. In order to do so, before identifying the cryptological signa laid by Ovid, we discuss the position and personality of Hyginus, the position of Pompeius Macer, who was also busy with the Palatine Library. We also endeavour to explain passages of various authors (Augustus, Ovid, Suetonius, Tzetzes on Callimachus), suggest emendations of some of these passages and discuss various issues pertaining to the achievement of ancient librarians and to ancient literary cryptology.